Characterization of main pulmonary artery and valve annulus region of piglets using echocardiography, uniaxial tensile testing, and a novel non-destructive technique - Sutherland, David W.; McEleney, Aisling; de Almeida, Matheus; Kajimoto, Masaki; Ventura, Giselle; Isenberg, Brett C.; Portman, Michael A.; Stapleton, Scott E.; Williams, Corin (Frontiers in Cardiovascular Medicine, 2022)
Characterization of cardiovascular tissue geometry and mechanical properties of large animal models is essential when developing cardiovascular devices such as heart valve replacements. These datasets are especially critical when designing devices for pediatric patient populations, as there is often limited data for guidance. Here, we present a previously unavailable dataset capturing anatomical measurements and mechanical properties of juvenile Yorkshire (YO) and Yucatan (YU) porcine main pulmonary artery (PA) and pulmonary valve (PV) tissue regions that will inform pediatric heart valve design requirements for preclinical animal studies. In addition, we developed a novel radial balloon catheter-based method to measure tissue stiffness and validated it against a traditional uniaxial tensile testing method. YU piglets, which were significantly lower weight than YO counterparts despite similar age, had smaller PA and PV diameters (7.6–9.9 mm vs. 10.1–12.8 mm). Young’s modulus (stiffness) was measured for the PA and the PV region using both the radial and uniaxial testing methods. There was no significant difference between the two breeds for Young’s modulus measured in the elastic (YU PA 84.7 ± 37.3 kPa, YO PA 79.3 ± 15.7 kPa) and fibrous regimes (YU PA 308.6 ± 59.4 kPa, YO PA 355.7 ± 68.9 kPa) of the stress-strain curves. The two testing techniques also produced similar stiffness measurements for the PA and PV region, although PV data showed greater variation between techniques. Overall, YU and YO piglets had similar PA and PV diameters and tissue stiffness to previously reported infant pediatric patients. These results provide a previously unavailable age-specific juvenile porcine tissue geometry and stiffness dataset critical to the development of pediatric cardiovascular prostheses. Additionally, the data demonstrates the efficacy of a novel balloon catheter-based technique that could be adapted to non-destructively measure tissue stiffness in situ.